Analisis Dampak Kehilangan Waktu Dan Biaya Operasi Akibat Antrian Pesawat Di Bandara Internasional Soekarno-Hatta - Raga, Paulus; Irenita, Novembriani; Agustin, Muhammad Fadillah (Jurnal Sistem Transportasi & Logistik, 2023)
Soekarno-Hatta International Airport is the largest main airport in Indonesia with 3 runway facilities with 2 dependent runways and 1 independent runway. The purpose of this study is to determine the cost of aircraft operational queues and the expected average waiting time of aircraft when taking off and landing in 2023 and forecasting in 2025 to determine developments when conditions return to normal. In this study, the queuing system method is used, the data used is from January - December 2023 and data from 2014 - 2018 for 2025 forecasting analysis. The results of the study showed that the waiting time for aircraft in 2023 was 0.00491 hours, with a waste of operational costs reaching Rp91,594,539,917.00. In this case, Soekarno-Hatta International Airport can minimize the time and cost by using 3 runways independently, because the costs incurred to operate the 3 runways are the same as the costs incurred for operating 2 dependent runways and 1 independent runway but the resulting time and cost can be further minimized.